4(5m-3m)-9=3m-4

Simple and best practice solution for 4(5m-3m)-9=3m-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(5m-3m)-9=3m-4 equation:


Simplifying
4(5m + -3m) + -9 = 3m + -4

Combine like terms: 5m + -3m = 2m
4(2m) + -9 = 3m + -4

Remove parenthesis around (2m)
4 * 2m + -9 = 3m + -4

Multiply 4 * 2
8m + -9 = 3m + -4

Reorder the terms:
-9 + 8m = 3m + -4

Reorder the terms:
-9 + 8m = -4 + 3m

Solving
-9 + 8m = -4 + 3m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-3m' to each side of the equation.
-9 + 8m + -3m = -4 + 3m + -3m

Combine like terms: 8m + -3m = 5m
-9 + 5m = -4 + 3m + -3m

Combine like terms: 3m + -3m = 0
-9 + 5m = -4 + 0
-9 + 5m = -4

Add '9' to each side of the equation.
-9 + 9 + 5m = -4 + 9

Combine like terms: -9 + 9 = 0
0 + 5m = -4 + 9
5m = -4 + 9

Combine like terms: -4 + 9 = 5
5m = 5

Divide each side by '5'.
m = 1

Simplifying
m = 1

See similar equations:

| 4x-31/3=182/3 | | 5t-(3t+14)=2t-14 | | 5x^4-3x^2-1=0 | | 76=2x+16 | | x+2n=15n+23 | | 3a+13=9a | | 13-9x=133-37x | | x+2n=5n+23 | | 3x+(2/5)=4x+(4/5) | | (8x+12)=((5x-5)2) | | 6x-7=79-2x | | 9+4x=18x | | 9y-10=5y-54 | | 6x^4-12x^2= | | (3-4)+4*3*-3= | | 72x^2+56x/9x-7 | | 7(2x-8)-6=14x-62 | | 4(m-2)-7+2m=6(m+5) | | (8x+12)=(5x-5) | | 3z+7=35 | | 6(1/3)= | | 0*X=5 | | 8r+-5=51 | | 16+-9-2(4*3*1/2)= | | 8/3-2i | | -10+2m=8 | | 90+.4x=X | | 16+x^2=49 | | 5/4a+2=22 | | 8/(3-2i) | | 9y+-10=5y+54 | | -4(3y-10)+2(2y+9)= |

Equations solver categories